Effect of an educational intervention on the level of knowledge, healthy lifestyle practices and metabolic control of patients in the diabetes mellitus 2 program of the department of Concepción, Paraguay: a single-blind experimental study - Echeverría Acosta, Luciana; Giménez, Lorena Elizabeth; Ruiz Romero, Miguela; Giménez Legal, Eva Natalia; Ortiz Galeano, Ignacio (Medicina Clínica y Social, 2025)
Introduction: Diabetes mellitus 2 is considered the new epidemic of the 21st century, its incidence and prevalence are increasing rapidly, and it is considered the second cause of death in Paraguay. Objective: To evaluate the effect of an educational intervention on the level of knowledge, healthy lifestyle practices, and metabolic control of patients in the Diabetes Mellitus 2 Program of the Department of Concepción. Methodology: Experimental, single-blind study in patients of the Diabetes Mellitus 2 Program of the Department of Concepción, year 2023. A simple random sampling was used, including 158 patients for the intervention group and 320 patients for the control group. The sample size was calculated with the Epidat 3.1 statistical program. For data collection, diabetic patients were summoned to the health services of their community and were collected through an interview in two periods, pre and post intervention, using two validated questionnaires: Diabetes knowledge Questionnaire 24 to measure the level of knowledge and for the healthy lifestyle the IMEVID instrument. In the intervention group an educational program was implemented for 3 months. Results: 480 patients participated, mean age 60.7 years ± 1, female sex control group 76.9% and intervention group 75.3%. Significant difference was found in the level of knowledge, lifestyle, metabolic control and adherence to treatment between the intervention and control group after three months of educational intervention (p
Keywords: Diabetes mellitus; educational intervention; level of knowledge; lifestyle; metabolic control; adherence to treatment